2008
DOI: 10.1021/ef7004207
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Combustion Characteristics of Various Gaseous Fuels

Abstract: The combustion of a gas-fired pulse combustor was simulated using a computation fluid dynamic model to understand the flame structure, gas flow, and combustion characteristics in the burner and the resulting pulsation phenomenon. The specific impulse and thrust output to power input are computed and compared. Some typical gaseous fuels such as low molecular weight hydrocarbons, high molecular weight hydrocarbons, biofuels, and mixed fuels are tested via simulation of the pulse combustor, and their operation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Therefore, the inlet condition is prescribed explicitly in a majority of the models, which directly defines the pulsation frequency. Only the models by Benelli et al [28], Tajiri and Menon [30], and Zhonghua et al [33,35] treat the inlet condition in a way which allows the formation of oscillations with a frequency corresponding to the combustion kinetics.…”
Section: Process Model Of a Pulsation Reactormentioning
confidence: 99%
“…Therefore, the inlet condition is prescribed explicitly in a majority of the models, which directly defines the pulsation frequency. Only the models by Benelli et al [28], Tajiri and Menon [30], and Zhonghua et al [33,35] treat the inlet condition in a way which allows the formation of oscillations with a frequency corresponding to the combustion kinetics.…”
Section: Process Model Of a Pulsation Reactormentioning
confidence: 99%
“…More and more, developed modern commercial CFD codes based on universal equations and models of turbulence, heat transfer and combustion, according to the authors of this article, if properly used, can significantly support the study of pulsating combustion. In particular, researchers use calculation packages to assess the parameters of the process taking place inside the combustion chamber, e.g., flame structure [34], mixture composition [35], emission of pollutants [11,36] or the evaporation of fuel droplets inside the combustion chamber [37].…”
Section: Introductionmentioning
confidence: 99%
“…In the vast majority of the analysed publications [34,37,45,46], the authors decided on the k-ε turbulence model. The choice is motivated by the fact that it is a well-proven model, constituting a compromise between the demand for computing power and the results achieved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance combustion efficiency and improve carbon anode baking homogeneity [5], a recent development is the use of pulsating flame jets in most of the anode baking furnaces. Several studies are carried out on the application of pulse combustion in several industrial usages [6][7]. It is reported that…”
Section: Introductionmentioning
confidence: 99%